Computer graphic display method for visualizing three-dimensional biological structures - Jiménez, J; Santisteban, A; Carazo, J M; Carrascosa, J L (Science (American Association for the Advancement of Science), 1986)
A computer graphic display method that produces two-dimensional perspective views of three-dimensional objects is presented. The method is applied to the reconstruction at a resolution of 2.2 nanometers of the neck of bacteriophage phi 29, obtained from transmission electron micrographs processed by the direct Fourier method. The combined use of directed illumination, reflectance models, color, and different levels of transparency provides a powerful tool for a better interpretation of the three-dimensional structure, allowing improved correlation with genetic, structural, and biochemical data.